The unfinished Enlightenment : description in the age of the encyclopedia - Stalnaker, Joanna (Cornell University Press, 2010)
In The Unfinished Enlightenment, Joanna Stalnaker offers a fresh look at the French Enlightenment by focusing on the era's vast, collective attempt to compile an ongoing and provisional description of the world. Through a series of readings of natural histories, encyclopedias, scientific poetry, and urban topographies, the book uncovers the deep epistemological and literary tensions that made description a central preoccupation for authors such as Buffon, Bernardin de Saint-Pierre, Diderot, Delille, and Mercier. Stalnaker argues that Enlightenment description was the site of competing truth claims that would eventually resolve themselves in the modern polarity between literature and science. By the mid-nineteenth century, the now habitual association between description and the novel was already firmly anchored in French culture, but just a century earlier, in the diverse network of articles on description in Diderot and d'Alembert's Encyclopédie and in the works derived from it, there was not a single mention of the novel. Instead, we find articles on description in natural history, geometry, belles-lettres, and poetry. Stalnaker builds on the premise that the tendency to view description as the inevitable (and subservient) partner of narration-rather than as a universal tool for making sense of knowledge in all fields-has obscured the central place of description in Enlightenment discourse. As a result, we have neglected some of the most original and experimental works of the eighteenth century.